Evaluation of substrates for mass multiplication of fungal biocontrol agents Trichoderma harzianum and T. virens - ANANDARAJ, Y R SARMA, M G PRAKASH, K VINAYA GOPAL, M (Journal of Spices and Aromatic Crops, 1999)
Evaluation of four substrates (neem cake, farm yard manure, coffee husk and tea waste) for the mass multiplication of fungal biocontrol agents Trichoderma harzianum and T. virens indicated that tea waste was the best media. The cultures mass multiplied in tea waste could also be stored for 3 months without much reduction in the population of biocontrol agents.